SUPPLEMENTARY FEEDING (PMT) PROGRAM FOR TODDLERS FROM LOCAL FOOD AT PANUNGGANGAN PUBLIC HEALTH CENTER, TANGERANG CITY, 2023 - Eminita Krina; Dewi Purnamawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
Background: One of the strategies for dealing with nutritional problems in toddlers is the provision of supplementary feeding (PMT) made from local food which is available, easy, and affordable. Purpose: This study aims to describe the local food-based PMT program for undernourished toddlers with a BB/U index at the Panunggangan Public Health Center, Tangerang City in 2023. Method: this research is descriptive, the population is mothers who have under nutritional status with an underweight indicator for BB/U at the Panunggangan Public Health Center. The sample was determined based on the needs of 50 toddlers, using a purposive sampling technique, data was collected by anthropometric measurements of toddlers and interviews with mothers of toddlers, and the data was analyzed univariately. Results: During 14 days, local food-based PMT was given to 50 toddlers according to the criteria at the Panunggangan Health Center, Tangerang City. More than half of the respondents were male (52%), most of them were 23 months old (74%), there was an increase in body weight in 44 toddlers (88%), there was a change in the nutritional status of the weight/age indicator in 9 toddlers (18%), toddlers' acceptance of PMT (likes 74%), however only 28% of mothers of toddlers make their snacks, the rest buy instant snacks because they don't have varied cooking skills. Conclusion: There are many benefits to be gained from implementing the PMT program made from local food for toddlers which has a positive impact on health status, nutrition, and other factors. Suggestion: it is necessary to increase the skills of cadres and mothers of toddlers in processing PMT based on local food